Guidelines for the Prevention and Treatment of Chronic Hepatitis B (Version 2022) - Hong You; Fu-Sheng Wang; Taisheng Li; Xiaoyuan Xu; Yameng Sun; Yuemin Nan; Guiqiang Wang; Jinlin Hou; Zhongping Duan; Lai Wei; Jidong Jia; Hui Zhuang; et al. (Medicine, 2023)
Abstract. To facilitate the achieving of the goal of “eliminating viral hepatitis as a major public health threat by 2030” set by the World Health Organization, the Chinese Society of Hepatology together with the Chinese Society of Infectious Diseases (both are branches of the Chinese Medical Association) organized a panel of experts and updated the guidelines for prevention and treatment of chronic hepatitis B in China (version 2022). With the support of available evidence, this revision of the guidelines focuses on active prevention, large-scale testing, and expansion of therapeutic indication of chronic hepatitis B with the aim of reducing the hepatitis B–related disease burden.